Hemagglutination activities and phenotypic expressions of fifty-five S. agalactiae isolates consisted of 19 standard and 36 field isolates from subclinical mastitis cattle were observed. Five (eighteen); 3 (4); 2 (7); 1 (2); and 5 (11) isolates (numbers in brackets indicated field isolates) were able to hemagglutinate cattle, horse, sheep, chicken, and human erythrocytes, respectively. The distribution of hemagglutination pattern was discissed in this paper. - Iwan Harjono Utama; Anak Agung Sagung Kendran; I Wayan Teguh Wibawan; Fachriyan Hasmi Pasaribu (Media Veteriner, 2000)
Hemagglutination activities and phenotypic expressions of fifty-five S. agalactiae isolates consisted of 19 standard and 36 field isolates from subclinical mastitis cattle were observed. Five (eighteen); 3 (4); 2 (7); 1 (2); and 5 (11) isolates (numbers in brackets indicated field isolates) were able to hemagglutinate cattle, horse, sheep, chicken, and human erythrocytes, respectively. The distribution of hemagglutination pattern was discissed in this paper.